ANALYSIS OF EMPLOYEE PERFORMANCE AT PT PERKEBUNAN NUSANTARA IV UNIT KEBUN SIDAMANIK - Butarbutar, Marisi; Efendi, Efendi; Fadhila, Suci; Sitompul, Rosalinda Septiani; Nainggolan, Pinondang (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2023)
This study aims to analyze employee performance at PT Perkebunan Nusantara IV Sidamanik Unit. Research method with survey, data collection through interviews and questionnaires. The unit of analysis in this study were 45 employees of the production department. Data were analyzed with qualitative analysis. The results showed that employee performance was good but not optimal, with the highest dimension in the dimension of job satisfaction, and the lowest value was in the dimension of discipline. To optimize employee performance by disciplining employees through strict sanctions in accordance with the company's standard operating procedures.